2018
DOI: 10.1080/10439463.2018.1434177
|View full text |Cite
|
Sign up to set email alerts
|

The use of rapid identification information at the crime scene; similarities and differences between English and Dutch CSIs

Abstract: The use of rapid identification information at the crime scene; similarities and differences between English and Dutch CSIs de Gruijter, Madeleine; de Poot, Christianne J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…This clear articulation of the purpose of scene examination in England and Wales reflects other findings of experimental studies (e.g., de Gruijter & de Poot, 2018). Discussing the influence of rapid identification technologies on the practices of CSEs at crime scenes, these authors observed differences between English and Dutch CSEs, framing the Dutch CSEs positively through their work to reconstruct the event with English CSEs said to be "biased towards obtaining identifications of individuals" (de Gruijter & de Poot, 2018, p. 17).…”
Section: Learning and Doing Crime Scene Examination: Straddling Scientific And Investigative Practicessupporting
confidence: 77%
See 2 more Smart Citations
“…This clear articulation of the purpose of scene examination in England and Wales reflects other findings of experimental studies (e.g., de Gruijter & de Poot, 2018). Discussing the influence of rapid identification technologies on the practices of CSEs at crime scenes, these authors observed differences between English and Dutch CSEs, framing the Dutch CSEs positively through their work to reconstruct the event with English CSEs said to be "biased towards obtaining identifications of individuals" (de Gruijter & de Poot, 2018, p. 17).…”
Section: Learning and Doing Crime Scene Examination: Straddling Scientific And Investigative Practicessupporting
confidence: 77%
“…It may be that it leads you to intelligence‐based information or it may be for the prosecution (Crime Scene Examiner).This clear articulation of the purpose of scene examination in England and Wales reflects other findings of experimental studies (e.g., de Gruijter & de Poot, ). Discussing the influence of rapid identification technologies on the practices of CSEs at crime scenes, these authors observed differences between English and Dutch CSEs, framing the Dutch CSEs positively through their work to reconstruct the event with English CSEs said to be “biased towards obtaining identifications of individuals” (de Gruijter & de Poot, , p. 17). While this emphasis on identification is reflected in the ethnographic work described above, the quotation from Wilson‐Kovacs' study (2014, p. 771) and wider ethnographic work provide detailed accounts and insights into why this might be the case.…”
Section: Learning and Doing Crime Scene Examination: Straddling Scienmentioning
confidence: 75%
See 1 more Smart Citation
“…This scenario may influence the way new incoming information is interpreted, due to well-known cognitive processes such as confirmation bias and belief perseverance [11]. Recent research indicates that CSIs attach great importance to obtained database-matches [7]. The risk here lays in the fact that such results may become leading in the investigation when they are provided too soon, while alternative explanations for the findings should still be considered.…”
Section: Challenge 3: Subjective Interpretations Of Analysis Resultsmentioning
confidence: 99%
“…Depending on the context information provided and the expectation of the observer, traces or clues are interpreted consistent with either one or the other scenario [4,5]. Furthermore, important traces appear to be frequently overlooked when they are left at unexpected places [6,7].…”
Section: Challenge 1: Guiding Goals and Expectations Influencing The Perception Of Tracesmentioning
confidence: 99%